Fundamentals of deep brain stimulation for Parkinson's disease in clinical practice: part 1 - Camila Henriques de Aquino; Mariana Moscovich; Murilo Martinez Marinho; Lorena Broseghini Barcelos; André C. Felício; Matthew Halverson; Clement Hamani; Henrique Ballalai Ferraz; Renato Puppi Munhoz (Arquivos de Neuro-Psiquiatria)
Deep brain stimulation (DBS) is recognized as an established therapy for Parkinson's disease (PD) and other movement disorders in the light of the developments seen over the past three decades. Long-term efficacy is established for PD with documented improvement in the cardinal motor symptoms of PD and levodopa-induced complications, such as motor fluctuations and dyskinesias. Timing of patient selection is crucial to obtain optimal benefits from DBS therapy, before PD complications become irreversible. The objective of this first part review is to examine the fundamental concepts of DBS for PD in clinical practice, discussing the historical aspects, patient selection, potential effects of DBS on motor and non-motor symptoms, and the practical management of patients after surgery.